Wednesday 20 November 2013

Rules of Boolean Algebra

AND Operations (·)
0·0 = 0 A·0 = 0
1·0 = 0 A·1 = A
0·1 = 0 A·A = A
1·1 = 1 A·A' = 0

OR Operations (+)
0+0 = 0 A+0 = A
1+0 = 1 A+1 = 1
0+1 = 1 A+A = A
1+1 = 1 A+A' = 1

NOT Operations (')
0' = 1 A'' = A
1' = 0

Associative Law
(A·B)·C = A·(B·C) = A·B·C
(A+B)+C = A+(B+C) = A+B+C

Distributive Law
A·(B+C) = (A·B) + (A·C)
A+(B·C) = (A+B) · (A+C)

Commutative Law
A·B = B·A
A+B = B+A

Precedence
AB = A·B
A·B+C = (A·B) + C
A+B·C = A + (B·C)

De Morgan's Theorem
(A·B)' = A' + B' (NAND)
(A+B)' = A' · B' (NOR)

Redundance Law
A + AB = A
A (A + B) = A
0 + A = A
0 A = 0
1 + A = 1
1 A = A
A' A=0A+A=1
A+A'B=A+B
A(A'+B)=AB

A + A = A
A A = A
 AB+AB'=A
–(A+B)(A+B')=A

How to use Boolean algebra to simplify a sum of products expression

1. Try to find variables that can be factored out in such a way as to leave
terms that will simplify to zero or one. For example AB’ + AB =
A(B’+B) = A(1)=A.
2. If it helps you recognize patterns, rearrange the order of the terms in
the expression to group terms that have common variables together.
3. Keep the second distributive law in mind. It is used a great deal and
situations where it would help are often missed by people new to
Boolean expression simplification.
                                    A+BC = (A+B)(A+C)

The derivation of A+AB
A+AB     = A(1+B)
                = A(1)
                = A
The derivation of A+A’B
A+A’B    = (A+AB)+A’B
                = (AA+AB)+A’B
                = AA+AB+AA’+A’B
                = AA+AB+A’B
                = (A+A’)(A+B)
    = 1× (A+B)
                = (A+B)

The derivation of (A+B)(A+C)
(A+B)(A+C) = A+AC+AB+BC
                      = A(1+C)+AB+BC
                      = A×1+AB+BC
                      = A×1+ BC

                      = A+BC

No comments:

Post a Comment